Legal Analysis of Post-Mining Forest Rehabilitation and Reclamation - Hafik, Muhammad Makhrus; Sari, Qomara; Kottama, Ardhi Padma Yudha; Nugraha, Giadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Forests are land areas that are dominated by trees. It also contains a variety of flora and fauna that need to be protected sustainably. Indonesia is included in the top ten largest forests in the world. However, this position is in danger of declining as deforestation activities continue to occur due to commercialization and industrialization. The forest area is now being used as a mining area to dredge the produce. However, the absence of accountability from the regulator has made the company leave the former mine with holes in it. This study uses a descriptive study method with a qualitative approach. The result is that there are regulations that regulate permits in forest use, but there are also regulations that require miners to return through post-mining rehabilitation and reclamation. However, regulations issued through the Ministry of Energy and Mineral Resources have become a gap for miners to not be obliged to carry out reclamation and rehabilitation. It is then feared that it could cause an ecological disaster and loss of life. Besides that, it also threatens the existence of other forests because of regulations from the ministry so that its area is shrinking.